2021
DOI: 10.1155/2021/9919443
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Influencing Factors of Overweight and Obesity among Adult Residents of Western China: A Cross-Sectional Study

Abstract: Background. Overweight and obesity have become a serious health problem. There are a few data on the prevalence of overweight and obesity in Baoji city of western China, this study was conducted to investigate the epidemiologic features of overweight and obesity and explored influencing factors among Baoji adult residents. Methods. A cross-sectional study, including 36,600 participants aged above 15 years, was carried out in Baoji city in 2018. Each participant’s weight and height were measured, and demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Adeloye et al [23] in a study conducted in Nigeria, reported a higher prevalence of obesity among women. Inversely, a study conducted in China by Zheng et al [24] reported a higher prevalence of overweight among men compared to their female counterparts. Another study that noted a higher prevalence of obesity among men was conducted in the United States (USA) by Ogden et al [25].…”
Section: Discussionmentioning
confidence: 99%
“…Adeloye et al [23] in a study conducted in Nigeria, reported a higher prevalence of obesity among women. Inversely, a study conducted in China by Zheng et al [24] reported a higher prevalence of overweight among men compared to their female counterparts. Another study that noted a higher prevalence of obesity among men was conducted in the United States (USA) by Ogden et al [25].…”
Section: Discussionmentioning
confidence: 99%
“…In China, many scholars have studied the prevalence of different obesity indicators in adults and children. They found a general prevalence of obesity/overweight and that the prevalence and influencing factors vary between subgroups 4 , 7 , 16 , 19 , 20 . However, few studies have been conducted on specific populations.…”
Section: Introductionmentioning
confidence: 99%
“…4 Obesity and overweight are considered as precursors to a variety of comorbidities such as cardiovascular and renal disease, type 2 diabetes mellitus (T2DM), some malignancies, musculoskeletal disorders, and other chronic illnesses. 5 Most researchers agree that obesity is a complicated health condition that is influenced by a combination of biological, genetic, social, environmental, and behavioral determinants. 2 Different modalities are available for weight management.…”
Section: Introductionmentioning
confidence: 99%